Catalyst-free formation of vertically-aligned carbon nanorods as induced by nitrogen incorporation - Ritikos, R.; Rahman, S.A.; Gani, S.M.A.; Muhamad, M.R.; Yap, Y.K. (2011)
We found that nitrogen incorporation can induce the formation of vertically-aligned hydrogenated carbon nanorods without the use of catalysts. These nitrogen incorporated hydrogenated carbon nanorods (CN(x):H) were synthesized by radio-frequency plasma-enhanced chemical vapor deposition (PE-CVD). We have evaluated the structural and chemical evolution of these CN(x):H films as a function of the deposition duration by using high-resolution scanning electron microscopy (HRSEM), high-resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectroscopy (FTIR), and Auger electron spectroscopy. Results indicate that the incorporation of nitrogen is responsible to the formation of these nanorods. The alignment of the nanorods is enhanced at longer deposition period and is correlated to the increase in nitrogen contents and isonitrile bonds -N equivalent to C in the nanorods. The growth mechanism of this catalyst-free formation of nitrogen incorporated carbon nanorods is proposed. (C) 2011 Elsevier Ltd. All rights reserved.